New media encourages environmental participation in the digital era - Zulfikar, Meiby; Sarwoprasojo, Sarwititi; Hapsari, Dwi Retno; Handayanti, Riska (Priviet Social Sciences Journal, 2026)
With the development of new media, there is a great opportunity for society to become more involved in environmental issues. However, previous research still shows a significant gap: most studies focus on the use of social media as a source of information, whereas the mechanisms used by new media to shape significant engagement, from awareness to collective action, are not well understood. Additionally, as most research has been conducted in the context of developed countries, the dynamics of digital participation in developing countries, such as Indonesia, are less well represented. By contrast, the State of the Art (SOTA) shows a shift from linear communication models to patterns of “collaborative action” and “networked collaboration,” in which people work together through digital platforms using personalized stories, virtual communities, and citizen data. This study conducted a systematic literature review using a descriptive-qualitative approach. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) principles and environmental communication matrix theory were used in the screening process; the Theory of Planned Behavior, Affordances Platform, and Theory of Social Impact were combined to create a thematic analysis. The relationship between new media features, the way user interactions occur, and the emerging forms of environmental participation became the focus of the analysis. The synthesis results show that new media can function as a communication ecosystem that accelerates the dissemination of environmental information, strengthens social norms that support the environment, and expands participation—from symbolic actions, such as sharing content, to substantive actions, such as donations, reporting environmental conditions, digital campaigns, and community collaboration. However, significant challenges, such as disparities in digital literacy, algorithmic bias, information polarization, and the lack of online participation, leading to offline actions with real impact, were also found. To optimize the use of new media as a driver of sustainable environmental action, this study emphasizes that a more inclusive digital communication model, evidence-based content strategies, and cross-actor collaboration are necessary.